Dioxin exposure in breast milk and infant neurodevelopment in Vietnam. Issue 9 (6th February 2013) - Tai, Pham The; Nishijo, Muneko; Anh, Nguyen Thi Nguyet; Maruzeni, Shoko; Nakagawa, Hideaki; Luong, Hoang Van; Anh, Tran Hai; Honda, Ryumon; Kido, Teruhiko; Nishijo, Hisao
Abstract : Objectives: Dioxin levels in the breast milk of mothers residing near hot spots of dioxin contamination areas in South Vietnam remain much higher than in unsprayed areas, suggesting that fetuses and breast-fed infants may be exposed to high levels of dioxins. The present study investigated the association of infant neurodevelopment in early infancy and dioxin exposure during the perinatal period. Methods: The study involved 216 mother-infant pairs living near the Da Nang airbase, a dioxin contaminated area in Vietnam. Mothers and infants were followed from birth until infants were 4 months old. Dioxin levels in breast milk were measured to estimate the perinatal dioxin exposure, including the infant daily dioxin intake (DDI) via breastfeeding. Infant neurodevelopmental parameters, including cognitive, language and motor domains were assessed at approximately 4 months using the Bayley Scales of Infant and Toddler Development, third edition (Bayley-III). Results: The level of 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin and polychlorinated dibenzo-p-dioxins/furans-toxic equivalents in breast milk and the infant DDI showed significant inverse correlations with neurodevelopmental scores. When the subjects were divided into four groups according to dioxin levels in breast milk, the moderate and high DDI groups had significantly lower cognitive, composite motor and fine motor scores, and the high polychlorinated dibenzo-p-dioxins/furans-toxic equivalents group had significantly lower fine motor score than the low exposure group. For all domains, neurodevelopmental scores were decreased with increase in the level of 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin. Conclusion: The present study demonstrates a considerable impact of perinatal dioxin exposure on neurodevelopment in 4-month-old infants living in contaminated areas in Vietnam.